Ileocystoplasty with ureteral reimplantation into the afferent ileal limb for high-grade vesicoureteral reflux in a boy with lower urinary tract dysfunction - Hiroshi Shimura; Takahiko Mitsui; Masanari Fukasawa; Tatsuya Ihara; Satoru Kira; Norifumi Sawada; Masayuki Takeda (Elsevier, 2018)
We encountered a 12-year-old boy who had lower urinary tract dysfunction and high-grade vesicoureteral reflux (VUR) in a bilateral duplex system. Since febrile urinary tract infections (f-UTI) frequently occurred even after intermittent catheterization, we performed bladder augmentation and an anti-reflux procedure, reimplanting the four dilated ureters into the afferent ileal limb without creating a submucosal tunnel. The VUR was improved, and no f-UTI were seen after the surgery. The described anti-reflux procedure, which is based on bowel peristalsis, seems to be a feasible treatment for VUR in patients who undergo augmentation cystoplasty. Keywords: Augmentation, VUR, Bowel peristalsis